Ukrainian play remakes by the German playwrighter A. Kotzebu (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article is devoted to poetics of a remake-translator V. Kovalskiy. Analysis of the show-plays: playwright's utilization of concentration, composition and contrast.
Keywords: remake; micropoetics; macropoetics